Komposisi Jenis dan Kelmpahan Ikan Karang di Perairan Pulau Parang Kepulauan Karimunjawa Jepara - Wijanarko, Tutus; Munasik, Munasik; Ambariyanto, Ambariyanto (Departemen Ilmu Kelautan, Fakultas PerikanJurusan Ilmu Kelautan, Universitas Diponegoro)
Parang island is the most northwest island in the Karimunjawa islands, It has unique characteristic, namelyleeward and windwardwaters. It is suspected to be the factors that can affect the existence of coral reef ecosystem diversity and reef fish’s habitat.This study aims to determine the species composition and abundance of reef fish in the waters of Parang island, Karimunjawa.Data were collected by using abelttransectmethod(belt transect) along 75meter coastline. The results showed that the research location have a totally 1069 individuals. There were differences in the composition and abundance of reef fish in the waters in the east, south, west and north. The highest abundance of reef fish was found in the north side the island, there were 462 fish which composed of 20 species and 9 families. Family which has the highest species composition was Pomacentridae and Labridae. The lowest abundance of reef fish was found in the waters in the west side with 146 fish which was composed of 11 species of 5 family of reef fish, and species of fish that hasthe highest constituent of abundance was Family Pomacentridae and Labridae. There were 203 reef fish found on the south side of theParangisland thatborders directly with Kumbang Island, which was composed of 16 species, 8 family, and species of fish that has the highest constituent wereFamily Pomacentridae and Caesionidae. While in the waters of the eastern side the dominance fish was found Family Apogonidae fairly high as 144 individu, from the total 258 individu reef fish consisting of 15 species and 6 families.Differences incompositionandabundance species ofreef fishin the waters ofParang islandis presumably becauseof differences inthe life form condition ofcoral reef habitatfrom effect leeward and windward of Parangisland, Karimunjawa Islands.